SKILLS FOR DEVELOPING PEDAGOGICAL COMPETENCE IN FUTURE TEACHERS - Ravshanbek Rizomatovich Karimov (European Science Publishing, 2024)
Determining the essence and features of the organization of psychological and pedagogical support for the development of professional competence of a teacher requires solving a number of problems.
Keywords: competence, socio-pedagogical competence, teacher qualification characteristics, pedagogical technology, socio-pedagogical technology.